Current opportunities for the export of medical services in Russia - S. V. Russkikh; E. A. Tarasenko; S. I. Grin; M. T. Yugay; K. K. Kryukova; L. I. Moskvicheva (Фармакоэкономика, 2022)
Objective: to identify factors and barriers for the development of medical services export (MSE) in the Russian Federation (RF), to establish recommendations for its stimulation, and to promote Russia as an exporter of medical services in the international arena.Material and methods. An analysis of the practice of MSE organizing and regulatory documents of 2018–2021 was carried out, as well as the quantitative sociological survey of 184 doctors, healthcare managers and experts and the in-depth semi-structured interviews with 8 high-level healthcare experts conducted in 2020. The survey was performed using the “snowball” method. To increase the level of representativeness of the survey results, doctors, organizers and healthcare experts with current work experience in organizations and government bodies in the healthcare sector (Ministry of Health of the RF, Roszdravnadzor, Central Research Institute of Organization and Informatization of Public Health, etc.) were involved as respondents including practicing physicians and heads of medical organizations.Results. The aim of MSE state regulation and stimulation is to choose the optimal model for supporting inbound medical tourism (IMT) in the RF. At the moment, three models of supporting foreign citizens in the medical services market are developing: 1) creating expert medical consortia of leading medical clinics; 2) forming an infrastructure for agency support in the Russian IMT market, including the development of infrastructure in regional IMT markets with high, medium and low export potential; 3) paid medical services in all types of medical care are successfully provided in public and private clinics to foreign citizens who live, work or study in the RF on a permanent or temporary basis. The third model is а self-organizing patient flow of foreign citizens, uncontrolled by Russian medical organizations.Conclusion. The main strategic directions of MSE development for the growth of an organized and controlled patient flow in the RF are medical care services in the field of neurosciences, high-tech surgery and rehabilitation, reproductive medicine, immunotherapy of oncological diseases, and cross-border diagnostic services. It is necessary to take certain measures to stimulate MSE, including the introduction of international standards for the safety and quality of medical care, increasing the service component of the provision of medical services, building channels of marketing communications with foreign patients and the promotion of Russia as an exporter of medical services in the international arena.